PERLINDUNGAN HUKUM TERHADAP NASABAH ASURANSI PADA PERJANJIAN ASURANSI KESEHATAN DI PT ASURANSI RELIANCE INDONESIA - Putu Sekarwangi Saraswati; I Wayan Wisadnya (Universitas Mahendradatta, 2021)
This study aims to determine the legal protection of insurance customers in the health insurance agreement at PT Asuransi Reliance Indonesia and the legal consequences if the insurance company defaults on the health insurance agreement made in the health insurance agreement at PT Asuransi Reliance Indonesia between the company and the insurance customer. Legal protection for insurance customers in the health insurance agreement at PT Asuransi Reliance Indonesia is based on the rights of the insured as stipulated in the insurance agreement to provide compensation to the insured, if the insurance company defaults, the judiciary can provide legal protection in the form of a fair decision for the insured who harmed by the insurance company if proven in court. The legal consequences if the insurance company defaults on the health insurance agreement made, there will be sanctions for non-compliance with registration obligations, providing compensation to insurance customers, the imposition of administrative sanctions is carried out after a written warning is given, given a maximum of 2 (two) times each. for a maximum period of 10 (ten) working days, returning the rights of the insured to the premium that has been deposited, criminal sanctions, based on the provisions of Article 55 of Law Number 24 of 2011, Companies that do not carry out their obligations as referred to in Article 19 of Law Number 24 of 2011 paragraphs 1 and 2, shall be sentenced to a maximum imprisonment of 8 (eight) years or a maximum fine of Rp. 1,000,000,000, - (One Billion Rupiah).